PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN (BUDGETARY SLACK) DENGAN ASIMETRI INFORMASI, GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris pada Pemerintah Daerah Kabupaten Rokan Hilir) - Ferawati, Dian; -, Yusrarlaini; Savitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to test: 1) The effect of Budgetary Participation in the Budgetary Slack. 2) Effect of Budgetary Participation in Budgetary Paricipation in Budgetary Slack with Information Asymetry as Moderating Variabels. 3) Effect of Budgetary Slack with Leadership style as Moderating variables. 4) Effect of Budgetary Participation on Budgetary Slack with Organizational Commitmet as Moderating Variables. The population in this study is SKPD on Kabupaten Rokan Hilir. Data was collected by distributing questionnaires. The findings in this study are: 1) Budgetary Participation significant effect on the Budgetary Slack. Meaning that the first hypothesis in this study received. 2) Information Asymetry significant effect on the Budgetary Slack. Meaning that the second hypothesis in this study recaived. 3) Leader ship style significant effect on the budgetary slack. Meaning that the third hypothesis in this study received. 4) organizational Commitmen significant effect on the Budgetary Slack. Meaning that the fourth hypothesis in this study received. In this study suggested: 1) This research can then consider using a wider research object to the scope of the Province. 2) This study only took Budgetary Participation Variables as Independent Variables and Information Asymmetry, Leadership styles, Organitational Commitmen as Moderating Variables. Therefore to include other Variables that affect the Budget Participation, example: Organizational culture.Keywords: Budget Participation, Budgetary Slack, Information Asymmetry LeadershipStyle, Organizational Commitment